Specialised design for dementia - Habell, Martin (Perspectives in public health)
Demographic trends point to a fast-rising demand for elderly dementia care – but ordinary elderly care environments are unsuitable for dementia, which requires specialised accommodation. This paper concerns itself with the health and behaviour benefits of the special environment and not the available care and medication. Compared with traditional elderly care, space requirements are larger, there are security and care issues, as well as light, sleep, sensory and exercise aspects. The internal environment can be used for therapeutic benefit, using movement, memory trails, behaviour cues, signage, sun light therapy, light spectrum control and landscape. Special planning can mitigate antisocial behaviour, agitation, anxiety and confusion. It can provide scope for family involvement. To date, care has made blanket unspecialised provision. There is a need for a coherent and comprehensive approach to the total environment and to view it as a tool for care. This paper records the features developed in the design of specialised dementia care buildings by the author as part of a sequence of care homes evolved and adapted with feedback.